2017
DOI: 10.3324/haematol.2017.167742
|View full text |Cite
|
Sign up to set email alerts
|

Dose-adjusted EPOCH chemotherapy for untreated peripheral T-cell lymphomas: a multicenter phase II trial of West-JHOG PTCL0707

Abstract: The standard CHOP therapy for peripheral T-cell lymphoma has resulted in unsatisfactory outcomes and it is still not clear what is the optimal front-line therapy. We conducted a multicenter phase II study of dose-adjusted etoposide, doxorubicin, and cyclophosphamide with vincristine and prednisone (EPOCH) for untreated peripheral T-cell lymphoma patients. In this prospective study, 41 patients were treated with dose-adjusted-EPOCH as initial therapy: peripheral T-cell lymphoma-not otherwise specified, n=21; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Our analysis illustrates how such an exclusion can bias OS estimates. Not only in high-grade DLBCL, but also in BL,(Corazzelli et al, 2012; Dunleavy et al, 2013) MCL,(Ruan et al, 2015; Visco et al, 2013) and even PTCL,(Dupuis et al, 2015; Maeda et al, 2017) many phase 2 trials assert OS or even PFS of 70% or higher. Such trials can strongly influence clinical practice, but clinicians should be mindful of selection factors that produce these very favourable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis illustrates how such an exclusion can bias OS estimates. Not only in high-grade DLBCL, but also in BL,(Corazzelli et al, 2012; Dunleavy et al, 2013) MCL,(Ruan et al, 2015; Visco et al, 2013) and even PTCL,(Dupuis et al, 2015; Maeda et al, 2017) many phase 2 trials assert OS or even PFS of 70% or higher. Such trials can strongly influence clinical practice, but clinicians should be mindful of selection factors that produce these very favourable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutic regimens used have included DA-EPOCH and CHOP, which have successfully been used to treat patients with T-cell lymphomas. 33,34 In addition, SMILE, a promising chemotherapy for NK-cell malignancies, has also shown some efficacy in a subset of patients with T-cell CAEBV, although the numbers are still small. 23,35 For patients with HLH signs and symptoms, initiating HLH-directed treatment is required.…”
Section: Chemotherapymentioning
confidence: 99%
“… 41 A single arm phase 2 study investigated the use of DA-EPOCH (etoposide, prednisolone, vincristine, cyclophosphamide and doxorubicin). 42 This small trial (41 patients) reported after very short follow-up (median 24 months) showed favorable results with 2-year progression free survival (PFS) and overall survival (OS) of 53% and 73%, respectively. A larger study is needed to confirm these results.…”
Section: Frontline Treatmentmentioning
confidence: 97%